Clinical and economic benefits of de-escalating stress ulcer prophylaxis therapy in the intensive care unit: A quality improvement study. Issue 6 (November 2019) - Anstey, Matthew H; Litton, Edward; Palmer, Robert N; Neppalli, Sneha; Tan, Benedict J; Hawkins, David J; Krishnamurthy, Ravi B; Jacques, Angela; Sonawane, Ravikiran V; Chapman, Andrew R; Norman, Richard
Stress ulcer prophylaxis is commonly prescribed in the intensive care unit but can be inappropriately commenced or continued on discharge, exposing patients to potential harm. We aimed to evaluate whether a prescribing guideline, education program and pharmacist oversight would reduce inappropriate continuation of stress ulcer prophylaxis. This was a multicentre pre- (2014) and post- (2016) quality improvement study across five Australian intensive care units. Cost data were estimated using local information about prescribing patterns, and the relationship between long-term use and adverse events. A total of 531 patients were included in the pre- and 393 in the post-implementation periods. The proportion of hospital survivors inappropriately continued on stress ulcer prophylaxis reduced from 78/184 (42.4%) to 11/143 (7.7%) in the post-implementation period (odds ratio = 8.83; 95% confidence interval 4.47–17.45; P  < 0.0001). Clostridium difficile –associated disease reduced from 10 patients to one in the pre- to post-implementation groups. The extrapolated direct savings to all Australian intensive care units from reduced proton pump inhibitor prescribing are relatively small (AUD$2.08 million/year), but the reduction in complications has both benefits for patients and indirect savings of AUD$16.59 million/year nationally. In patients admitted to the intensive care unit, the introduction of a simple, bundled intervention resulted in a significant decrease in inappropriate continuation of stress ulcer prophylaxis at hospital discharge and a reduction in recognised complications, and substantial cost savings.